2003
DOI: 10.1038/sj.cgt.7700531
|View full text |Cite
|
Sign up to set email alerts
|

Ribozyme-mediated cleavage of the human survivin mRNA and inhibition of antiapoptotic function of survivin in MCF-7 cells

Abstract: Survivin is a new member of the inhibitor of apoptosis protein ( IAP ) family that is implicated in the control of cell proliferation and the regulation of cell life span. This protein is selectively expressed in most human carcinomas but not in normal adult tissues. To down -regulate a human survivin expression as a strategy for cancer gene therapy, we designed two hammerhead ribozymes ( RZ -1, RZ -2 ) targeting human survivin mRNA. RZ -1 and RZ -2 efficiently cleaved the human survivin mRNA at nucleotide pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
56
0
2

Year Published

2003
2003
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(60 citation statements)
references
References 44 publications
2
56
0
2
Order By: Relevance
“…9,11,13,34,35 In a preliminary investigation, we found that an exogenous apoptotic stimulus, for example, radiation, in combination with the knockdown of survivin expression increased the caspase-3 and caspase-7 activity 2.5-fold in the sarcoma cell line A-204, which expresses wild-type p53 (unpublished results). However, even after an apoptotic stimulus is applied, only a small percentage of cells from sarcoma cell lines undergoes apoptosis.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…9,11,13,34,35 In a preliminary investigation, we found that an exogenous apoptotic stimulus, for example, radiation, in combination with the knockdown of survivin expression increased the caspase-3 and caspase-7 activity 2.5-fold in the sarcoma cell line A-204, which expresses wild-type p53 (unpublished results). However, even after an apoptotic stimulus is applied, only a small percentage of cells from sarcoma cell lines undergoes apoptosis.…”
Section: Discussionmentioning
confidence: 87%
“…Furthermore, clonogenic survival of cells from each line was reduced by 65-86% (Fig 1c, Table 1). By using antisense oligonucleotides, 8,[10][11][12][34][35][36] ribozymes, 9,13,37 and siRNA (in a colon cancer cell line) 23 to knock down expression of survivin mRNA and protein, other investigators have observed a remarkable reduction in survivin mRNA that ranged from 70 to 90% and a reduction in survivin protein that ranged from 60 to 90%. The study conducted by Williams et al 23 has described the application of survivin-specific siRNA, which differs from the construct applied in our study, resulting in a reduction of survivin protein in colon cancer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…6 Because of its roles in reducing apoptosis, and stimulating cell division and proliferation, and its differential expression in cancers compared to normal tissues, Survivin is an attractive target for cancer gene therapy. 7 Thus far, different approaches have been taken to target Survivin, such as antisense oligonucleotides, 8 small interfering RNAs, 9 dominant negative mutants, 10 ribozymes 11 and triplex DNA-dependent kinase for cancer therapeutics. 12 However, none of these studies aiming at suppression of Survivin transcription can provide an ideal therapeutic approach.…”
Section: Introductionmentioning
confidence: 99%
“…The accumulated data from survivin studies on human cancers suggest that survivin expression in cancer is associated with cancer progression, poor prognosis, drug resistance, and shorter patient survival (Li, 2003). In vitro and in vivo studies targeting survivin with antisense oligonucleotides (Li et al, 1999;Chen et al, 2000;Olie et al, 2000;Xia et al, 2002), dominant-negative mutants (Li et al, , 1999Grossman et al, 1999a, b;O'Connor et al, 2000;Mesri et al, 2001), ribozymes (Pennati et al, 2002;Choi et al, 2003), triplex DNA-formation (Shen et al, 2003) and RNA interference (Ling and Li, 2004) have shown induction of apoptosis, reduction of tumorgrowth potential, and sensitization to chemotherapeutic drugs and other therapeutic approaches . These studies indicate that survivin is an excellent novel target for cancer therapeutics.…”
Section: Introductionmentioning
confidence: 99%